2016
DOI: 10.1371/journal.pone.0154684
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Efficient Elimination of Mitochondrial DNA from Cultured Cells

Abstract: Here, we document that persistent mitochondria DNA (mtDNA) damage due to mitochondrial overexpression of the Y147A mutant uracil-N-glycosylase as well as mitochondrial overexpression of bacterial Exonuclease III or Herpes Simplex Virus protein UL12.5M185 can induce a complete loss of mtDNA (ρ0 phenotype) without compromising the viability of cells cultured in media supplemented with uridine and pyruvate. Furthermore, we use these observations to develop rapid, sequence-independent methods for the elimination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 39 publications
(45 reference statements)
3
34
0
Order By: Relevance
“…1c). To rule out potential artefacts caused by the expression of mitochondrial pseudogenes integrated in the nuclear genome, we performed dsRNA staining in mtDNA-depleted HeLa cells obtained by either expressing the herpes simplex virus 1 (HSV-1) protein UL12.5M185 or human uracil– N -glycosylase (mUNG1)10. A lack of J2 signal confirmed that the dsRNA identified in our experiments can be wholly attributed to the mitochondrial genome (Extended Data Fig.…”
supporting
confidence: 64%
“…1c). To rule out potential artefacts caused by the expression of mitochondrial pseudogenes integrated in the nuclear genome, we performed dsRNA staining in mtDNA-depleted HeLa cells obtained by either expressing the herpes simplex virus 1 (HSV-1) protein UL12.5M185 or human uracil– N -glycosylase (mUNG1)10. A lack of J2 signal confirmed that the dsRNA identified in our experiments can be wholly attributed to the mitochondrial genome (Extended Data Fig.…”
supporting
confidence: 64%
“…The mitochondrial morphology changed and the mtDNA depletion induced mitochondrial fragmentation like that described in other Rho-0 cell lines generated by other methods [ 54 , 55 ]. The data obtained on mitochondrial respiration indicated that the 3a6 Rho-0 cells generated in this work have greatly impaired respiration, like that of a typical Rho-0 cell line [ 54 , 55 ]. All these characteristics indicate that hMSCs cultured with d4t are really Rho-0 cells.…”
Section: Discussionsupporting
confidence: 57%
“…A549 Rho0 cells were generated by continuous exposure for 3 month to ethidium bromide (50 ng/mL) as described previously [17]. Duplex PCR was used to validate the phenotype of A549 Rho0 cells [18]. Parental A549 and A549 Rho 0 cells were stained with MitoTracker Red or MitoTracker Deep Red at increasing concentrations.…”
Section: Methodsmentioning
confidence: 99%